Trace Amine Associated Receptor 1 (TAAR1) Modulation of Food Reward - Moore, Catherine F.; Sabino, Valentina; Cottone, Pietro (Frontiers in Pharmacology, 2018)
Eating disorders and some forms of obesity are characterized by addictive-like, compulsive eating behavior which contains numerous similarities with compulsive drug use. Food intake is in part mediated by reward and reinforcement processes that can become dysregulated in these disorders. Additionally, impairments in inhibitory control regulation of reward-related responding can cause or further exacerbate binge and compulsive eating. Dysfunctions in two neurotransmitter systems in the mesocorticolimbic pathway, dopamine and glutamate, are thought to contribute to maladaptive eating behaviors. The trace amine associated receptor 1 (TAAR1) system is a promising therapeutic target for compulsive eating behavior due to the role of TAAR1 in synaptic transmission and in the modulation of dopaminergic and glutamatergic signaling. In support of this notion, the TAAR1 agonist RO5256390 was found to decrease the reinforcing effects of palatable food-cues and to reduce binge-like and compulsive-like eating of palatable food. Additionally, prolonged, intermittent access to palatable food was shown to downregulate TAAR1 in the prefrontal cortex, suggesting a potential role for TAAR1 signaling in inhibitory control processes. Research into the role of TAAR1 in addiction, including TAAR1’s ability to modulate psychostimulant reward and reinforcement, bolsters support for TAAR1 agonism as a pharmacological treatment for compulsive eating and other addictive behaviors. This review summarizes the evidence for TAAR1 agonism as a promising therapeutic for compulsive eating behavior as well as the hypothesized mechanism responsible for these effects.